Twitter Research Synthesis for Health Promotion: A Bibliometric Analysis - Syed Hamd Hassan Shah; Saleha Noor; Atif Saleem Butt; Habiba Halepoto (Tehran University of Medical Sciences, 2021)
Background: This study enriched our understanding by systematically reviewing knowledge management twitter health (KMTH) articles extracted from Web of Science (WoS) using cartography analysis through VOSviewer-for the last 11 years. Methods: A total of 798 KMTH articles were found from 2009 to 2019, analyzed based on the most co-occurrence keywords of KMTH articles. Results: Three clusters emerged through cartography analysis; Cluster 1: Twitter as health education and health promotion platform; Cluster 2: Twitter as public health promotion platform and Cluster 3: Twitter as health sentiment platform through big data and machine learning. Conclusion: This study opened new avenues for all health care providers to utilize Twitter as a KM platform to promote health care. This is the first bibliometric analysis of KMTH publications according to our best knowledge.